Analysis of a downdraft gasifier for energy use of biomass waste applying computational fluid dynamics - Salazar Esquivel, Randall (2018)
A numerical modeling was performed that simulates the thermal and fluid-dynamic behavior and generation of chemical species from the biomass gasification process in a downdraft reactor using computational fluid dynamics (CFD). The simulation process was assumed as a stationary state, energy models, turbulence, transport of species and multiphase were established to adequately represent the equations that govern the transfer of mass, momentum and energy in the thermo-chemical degradation process of biomass. Variations in the airflow rate entered into the reactor were established in order to determine the optimum point of operation of the reactor. It was determined that using a flow rate of 400 l/min of air, the best results in terms of the quality of syngas produced are obtained, establishing this condition as the optimum operating point of the reactor.